2016
DOI: 10.1007/s00702-016-1582-x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effect of MAOA genotype and maternal prenatal smoking on aggressive behavior in young adulthood

Abstract: Findings on the etiology of aggressive behavior have provided evidence for an effect both of genetic factors, such as variation in the monoamine oxidase A (MAOA) gene, and adverse environmental factors. Recent studies have supported the existence of gene × environment interactions, with early experiences playing a key role. In the present study, the effects of prenatal nicotine exposure, MAOA genotype and their interaction on aggressive behavior during young adulthood were examined. In a sample of 272 young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In line with previous findings that a single gene polymorphism was not on its own related to aggressive behavior (e.g., Hygen et al, 2015 ; Hohmann et al, 2016 ; Tuvblad et al, 2016 ; Zhang Y. et al, 2017 ), our results didn’t show the main effect of MAOA T941G or COMT Ala22/72Ser polymorphism. However, MAOA T941G polymorphism was found to moderate the effect of interpersonal problems experienced by adolescents on aggressive behavior, specifically, adolescents with T allele were more likely to evince aggressive behavior when exposed to interpersonal problems.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with previous findings that a single gene polymorphism was not on its own related to aggressive behavior (e.g., Hygen et al, 2015 ; Hohmann et al, 2016 ; Tuvblad et al, 2016 ; Zhang Y. et al, 2017 ), our results didn’t show the main effect of MAOA T941G or COMT Ala22/72Ser polymorphism. However, MAOA T941G polymorphism was found to moderate the effect of interpersonal problems experienced by adolescents on aggressive behavior, specifically, adolescents with T allele were more likely to evince aggressive behavior when exposed to interpersonal problems.…”
Section: Discussionsupporting
confidence: 88%
“…MAOA knockout mice have been shown to exhibit elevated aggressive behavior ( Cases et al, 1995 ), but results from studies of the association between MAOA and aggressive behavior in humans were still inconsistent. A broader literature has shown that the low-activity MAOA genotype is associated with more aggressive behavior ( Caspi et al, 2002 ; Hart and Marmorstein, 2009 ; McDermott et al, 2009 ; Hohmann et al, 2016 ), while some other work has come to the opposite conclusion – that the high-activity MAOA genotype is associated with more aggressive behavior ( Manuck et al, 2000 ; Beitchman et al, 2004 ; Kinnally et al, 2009 ; Mcgrath et al, 2012 ). Still other studies have indicated that MAOA gene polymorphisms are not associated with aggressive behavior ( Fresan et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the roles genes play in disease pathogenesis has been enhanced by the study of interactions between genetic risk factors and the environment. Studies of these gene by environment interactions further highlight the importance of the environment in the development of physiological variability, and more recently, in keeping with the developmental origins of health and disease (DOHaD) hypothesis, pre and early postnatal exposures have been implicated as important to the development of neuropsychiatric disorders and their endophenotypic markers (Fortier et al, ; Hohmann et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, an emerging body of literature has indicated an interactive effect of MAOA genotype and prenatal adverse environments (e.g., mother’s smoking during pregnancy) on aggressive behavior in young adulthood. 54,55 The research literature also suggests that these individuals’ genetic sensitivity to the environment is for better and for worse: they are as likely to benefit disproportionately from supportive environments as to be disadvantaged by adverse ones. 56–58 And while initial studies on this so-called differential-susceptibility thesis—which has now mostly (but not always 59 ) been confirmed 60,61 by correlational studies, 62 a few randomized trials, 62 and a meta-analysis 62 —have focused primarily on family-based childhood adversity, more recent research demonstrates that adverse childhood environments may also include broader societal settings, such as conditions in schools and neighborhoods.…”
Section: Behavioral Genetics In Criminal Courtmentioning
confidence: 99%